DrumNet: an exchange for rural African entrepreneurs - Groh, Vince (Technical Centre for Agricultural and Rural Cooperation, 2003)
Vince Groh reports on DrumNet, which is building a network of information access points, or ´info-kiosks´, that offer combined microfinance and market information services for agricultural producers in Kenya. As mem